Socio-cultural factors influencing immunization of children in Ekiti State, Nigeria (2018)
Several studies have been conducted to urge efforts at reducing the rate of infant morbidity and mortality throughout the world. Scientific innovations and research for efficient immunization has been able to reduce the spread of poliomyelitis across the world and make this vaccine preventable disease a history. One hundred nursing mothers were interviewed on Socio cultural factors influencing immunization of children. Knowledge of immunization was observed to be average among the study population. Identified factors that limit immunization coverage include; attitude, culture, beliefs, religions, politics, economy, conspiracies, boycotts and human suspicions. Despite reasonable knowledge on immunization and its role in disease prevention, there is a need to improve availability of information on the importance of immunization and to chage parents’ negative beliefs and attitudes towards achieving total immunization coverage.